Cardiac Autonomic Nervous System Activity during Slow Breathing in Supine Position - Kai, Satoru (Rehabil Res Pract, 2021)
The purpose of this study is to clarify cardiac autonomic nervous system activity during slow breathing exercises in a supine position. Eighteen healthy young males were participated. Heart rate variability was measured for 5 minutes at rest, 5 minutes at slow breathing, and then 5 minutes at rest. As a result, the LF/HF ratio increased with slow breathing, but HF value did not change. We suggest that the increased LF/HF ratio may be due to increased airway resistance. Cardiac autonomic nervous system activity during slow breathing in the supine position was revealed.